2008
DOI: 10.1063/1.2971181
|View full text |Cite
|
Sign up to set email alerts
|

State-resolved studies of biexcitons and surface trapping dynamics in semiconductor quantum dots

Abstract: Biexcitons in strongly confined, colloidal CdSe quantum dots were investigated with excitonic state selectivity combined with 10 fs temporal precision. Within the first 50 fs, the first excited state of the biexciton was observed. By 100 ps, mixed character biexcitons were observed, comprised of a core exciton and a surface trapped exciton. The size dependence of the biexciton binding energies is reported for these specific biexcitons. Analysis of the spectral signatures of each biexcitonic state yields a quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

49
343
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(396 citation statements)
references
References 57 publications
49
343
1
1
Order By: Relevance
“…[31,32] The positive signal of the photoinduced absorption (PA) around l pr = 500 nm is a consequence of a shift of the 1P(e)-1P 3/2 (h) optical transition due to coulomb interactions between the excitons produced by the pump and the probe pulse. [31][32][33] This shift also explains the additional bleach of the band around l pr = 450 nm. However, also a higher transition involving the 1S(e) can contribute to this negative signal.…”
Section: /Mvmentioning
confidence: 88%
“…[31,32] The positive signal of the photoinduced absorption (PA) around l pr = 500 nm is a consequence of a shift of the 1P(e)-1P 3/2 (h) optical transition due to coulomb interactions between the excitons produced by the pump and the probe pulse. [31][32][33] This shift also explains the additional bleach of the band around l pr = 450 nm. However, also a higher transition involving the 1S(e) can contribute to this negative signal.…”
Section: /Mvmentioning
confidence: 88%
“…Most efforts thus far have utilized transient absorption to determine biexcitonic binding energies, the biexcitonic Stokes shift, the size dependence of these properties, and lifetimes of the biexciton [1,4,[14][15][16]. Sewall et al [14] have found that both the apparent biexciton binding energy and the biexciton Stokes shift are larger than the corresponding values for the single ground state exciton.…”
Section: Experimental Investigations Of Fine Structurementioning
confidence: 97%
“…This involves excitation into high energy bands of the NC and the production of multiple excitons at lower energy levels. As a result, many recent studies have examined higher multiexcitonic states, their lifetimes, and relaxation mechanisms to lower lying excitonic states [1,4,[14][15][16][17]. However, despite the great interest in this phenomena, very little is known about the electronic structure of these excitons, in particular the fine structure, since the inhomogeneous broadening of samples and the density of states [18] has proven to be prohibitive to experimental study of these states.…”
Section: Introductionmentioning
confidence: 97%
“…that typically occurs in the ps-time scale. [38,124] This slow process may be caused by an early relaxation of photoexcited carriers, e.g. electrons, into higher-energy conduction band minima, from which electrons eventually relax to the lowest energy minimum of the conduction band.…”
Section: Transient Absorption Spectroscopymentioning
confidence: 99%